2004
DOI: 10.1242/dev.00920
|View full text |Cite
|
Sign up to set email alerts
|

rigor mortisencodes a novel nuclear receptor interacting protein required for ecdysone signaling duringDrosophilalarval development

Abstract: Pulses of the steroid hormone ecdysone trigger the major developmental transitions in Drosophila, including molting and puparium formation. The ecdysone signal is transduced by the EcR/USP nuclear receptor heterodimer that binds to specific response elements in the genome and directly regulates target gene transcription. We describe a novel nuclear receptor interacting protein encoded by rigor mortis (rig) that is required for ecdysone responses during larval development. rig mutants display defects in molting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 54 publications
5
41
0
Order By: Relevance
“…rigor mortis is an essential gene, and mutants therein display significant larval lethality; animals that escape the initial wave of larval lethality are developmentally delayed and fail to pupate (Gates et al, 2004). These phenotypes are strikingly similar to those of the Smn F and Gemin3 alleles described in this work.…”
Section: The Drosophila Smn Complex and Ecdysone Signalingsupporting
confidence: 71%
See 1 more Smart Citation
“…rigor mortis is an essential gene, and mutants therein display significant larval lethality; animals that escape the initial wave of larval lethality are developmentally delayed and fail to pupate (Gates et al, 2004). These phenotypes are strikingly similar to those of the Smn F and Gemin3 alleles described in this work.…”
Section: The Drosophila Smn Complex and Ecdysone Signalingsupporting
confidence: 71%
“…These phenotypes are strikingly similar to those of the Smn F and Gemin3 alleles described in this work. Thummel and colleagues have shown that rig/dGem5 interacts with several members of the ecdysone signaling pathway required for initiation of puparium formation (Gates et al, 2004). Mammalian Gemin5 is also involved in signal transduction (Kim et al, 2007).…”
Section: The Drosophila Smn Complex and Ecdysone Signalingmentioning
confidence: 99%
“…Our present work reveals a novel mechanism of interaction among transcriptional regula-tors and a coactivator, which allows the functional integration of multiple transcriptional factors and enables the outputs of particular signaling pathways to be activated in a stage-specific manner. In recent years, several cofactors, including Bonus, NURF, Rig, SMRTER, Taiman, and TRR, have been implicated in ecdysone signaling during Drosophila development (1,2,4,12,38,43). In this study, we have shown that the coactivator FISC acts as a bridge between ␤Ftz-F1 and EcR/USP in the formation of the multiprotein complex, while there is no detectable direct physical attachment between ␤Ftz-F1 and EcR/USP.…”
Section: Discussionmentioning
confidence: 63%
“…It is conceivable that Dhh1 and Rigor mortis have adopted novel functions in a different context because they rapidly diverge from their ancestors (28). Consistent with this notion, a function of Rigor mortis in ecdysone signaling has been described (29).…”
Section: Discussionmentioning
confidence: 81%